Balancing conservation and use with heritage management, a dilemma for heritage institutions in Zimbabwe: case study: Nharira hills - Mudaose, Simbarashe (Midlands State University, 2017)
The study used a qualitative approach as to understand the need to balance conservation and use with heritage management in Zimbabwe. The aim of the study was to assess whether Zimbabwean heritage institutions have balanced mining use with the conservation of heritage places. In achieving the aim of the study, the research was based on the following objectives to assess whether NMMZ recognise mining company as a stakeholder of Nharira hills, to assess whether the mining use of the site ,is a threat to rock art conservation and to assess how other heritage authorities have balanced mining use and conservation of heritage places. Using the case study from Rio Tinto in Oyu Tolgoi Mongolia as the bench mark bases on how conservation and use can be balanced with heritage management, it state for the need to create acceptable limits of change as to balance developers’ interests with heritage conservation. This also led to the understanding that the granite miners at Nharira hills are the stakeholders of the heritage place. On the other hand, the research finds out that there are no predetermined agreement on which mining might operate hence rock art at Nharira hills is facing threats from mining use. The reason behind that was that, the granite miners are excluded from decisions and activities that have to do with the heritage place. Recommendations were also given which include the need to create the acceptable limits of change, the need to consider the developers’ interests on heritage places and the mining company should contribute to the development of the local community. Failure to consider the above recommendations, this will led to the loss of rock art at Nharira hills.